ANALISIS FIQIH INDUSTRI HALAL - Abu Bakar, Arifa Pratami (Fakultas Agama Islam, 2021)
The halal industry, which includes food, beverage, drug, cosmetic and other products, all of which are only regulated in the book of fiqh, is now regulated in laws and government regulations which are a new paradigm in regulating product halalness. Thus, from now on, it has been ensured that there is legal certainty and protection for consumers and producers for halal food, beverages, drugs, cosmetics and other halal products as a logistical consequence of the paradigm shift, guaranteeing legal certainty for halal products and protection for consumers and producers. besides being the responsibility of the individual and the ulama, it is also the responsibility of the government. Maqasid ash-shari'ah is not only the most decisive factor in producing sharia economic products that can play a dual role as a means of social control and socio-economic engineering to realize human benefit, but more than that, maqasid ash-syari' ah can provide a philosophical and rational dimension to sharia economic law products that are born in contemporary sharia economic ijtihad activities.